Combination of plant metabolites hinders starch digestion and glucose absorption while facilitating insulin sensitivity to diabetes - Huang, Xin; Lin, Kaihuang; Liu, Sinian; Yang, Junxiong; Zhao, Haowei; Zheng, Xiao-Hui; Tsai, May-Jywan; Chang, Chun-Sheng; Huang, Liyue; Weng, Ching-Feng (Frontiers in Pharmacology, 2024)
Introduction: Diabetes mellitus (DM), a common endocrine disease, is attributable to the interaction of genetic and environmental factors, and remarkably type 2 DM (T2DM) accounts for approximately 90% of all cases. Current DM treatments of medicines have some adverse or undesirable effects on patients, necessitating the usage of alternative medications.To overcome low bioavailability of plant metabolites, this study was screened all entities firstly through the prediction of pharmacokinetics, network pharmacology and molecular docking. And the experiment was further identified combination of anti-diabetic phytoactive molecules (rosmarinic acid, RA; luteolin, Lut; resveratrol, RS) accompanied with the evaluation of in vitro (α-Amylase inhibition assay) and diabetic mice test (OGTT and OSTT) for the maximal response in validating starch digestion and glucose absorption concomitant with facilitating insulin sensitivity.The results revealed that these metabolites achieved all the solicited criteria including ADMET, drug likeness, Lipinski rule. To disclose the underlying mechanism in diabetic hyperglycemia and T2DM treatment, network pharmacology was executed via regulatory network, PPI network, GO and KEGG enrichment analysis. Furthermore, combinatory metabolites had an adequate prediction in silico output (α-Amylase, α-Glucosidase, Pancreatic lipase for ameliorating starch digestion; SGLT-2, AMPK, Glucokinase, Aldose reductase, Acetylcholinesterase, Acetylcholine M2 receptor under mediating glucose absorption; and GLP-1R, DPP-IV, and PPAR-γ under regulating insulin sensitivity), in vitro α-Amylase inhibition, and in vivo efficacy tests in OSTT versus Acarbose and in OGTT versus Metformin and insulin for nutraceuticals against T2DM.Discussion: These results extraordinarily demonstrated that the combination of RA, Lut, and RS might be exploiting multi-target therapy for prospectively antihyperglycemic phyto-pharmaceuticals by hindering starch digestion, glucose absorption and facilitating insulin sensitivity.